2020
DOI: 10.1186/s12877-020-01687-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of financial stress on self-rereported health and quality of life among older adults in five developing countries: a cross sectional analysis of WHO-SAGE survey

Abstract: In developing countries, older adults (65 years of age and above) share an increased vulnerability to catastrophic health expenditures and financial stress which can have significant bearing on their health and well-being. Currently, research evidence on how financial stress correlates with health and well-being among older adults in the developing countries is limited. Therefore, in this study, we aimed to assess the relationship between financial stress and subjective 1) health, 2) depression, 3) quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 35 publications
5
33
0
Order By: Relevance
“…Good financial health appeared to be a positive correlate of physical and mental health among older women. In line with previous research ( Huang et al, 2020 ), a lower level of financial strain was associated with better self-perceived physical and mental health. The associations between financial health and well-being can be both direct and indirect: On one hand, better financial health may imply better resources to promote health in general; on the other hand, financial status may have some extra indirect effects on seniors’ health as financial instability could be a risk factor for family conflicts and violence ( Chang & Levy, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…Good financial health appeared to be a positive correlate of physical and mental health among older women. In line with previous research ( Huang et al, 2020 ), a lower level of financial strain was associated with better self-perceived physical and mental health. The associations between financial health and well-being can be both direct and indirect: On one hand, better financial health may imply better resources to promote health in general; on the other hand, financial status may have some extra indirect effects on seniors’ health as financial instability could be a risk factor for family conflicts and violence ( Chang & Levy, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…Other studies identifying aspects of life that are important to the wellbeing of Indigenous Australians also found that employment, education and money are needed to achieve good wellbeing [ 6 , 10 , 11 ]. Our results are consistent with previous studies in other populations that identified important socioeconomic impacts on wellbeing or quality-of-life, including financial stability for respondents in China, Ghana, India, South Africa, Russia and the United States [ 12 , 13 ], employment in the general Australian population [ 14 ], and higher education in the United States [ 13 ]. Socioeconomic disadvantage is consistently associated with poorer health outcomes for Indigenous Australians with cancer [ 15 ], cardiovascular disease [ 16 , 17 ], psychological distress [ 18 ], and liver cirrhosis [ 19 ], and have been associated with potentially preventable hospital admissions [ 20 ].…”
Section: Main Textsupporting
confidence: 92%
“…We found that respondents reporting lower financial stability had lower baseline wellbeing and HRQoL. The association between financial instability and reduced wellbeing and HRQoL has been described in other populations, however this link is unclear for Aboriginal and Torres Strait Islander people 28,29 . We found that respondents with the least financial stability had greater declines in wellbeing over time, while those with the most financial stability experienced the greatest declines in HRQoL.…”
Section: Discussionsupporting
confidence: 58%